Evolution and Innovation of Ship Propulsion Technology: From Paddle Power to Electric and Wind-Assisted Hybrid Systems for a Sustainable Maritime Future - Mastiadi Tamjidillah; Elwas Cahya Wahyu Pribadi; Abdul Ghofur; Rachmat Subagyo; Ma’ruf (International Journal of Marine Engineering Innovation and Research, 2026)
Ship propulsion has evolved significantly over thousands of years, from the use of simple paddles around 40,000 BCE to modern advanced systems driven by diesel engines, steam turbines, nuclear reactors, electric motors, and wind power. This systematic literature review aims to synthesize current knowledge on ship propulsion systems, highlighting technological advancements, energy efficiency, and environmental impacts. By analyzing various studies through a qualitative approach and the PRISMA framework, this research identifies three main themes: advanced propulsion systems, propulsion optimization, and hybrid technology integration. The results show that while diesel engines remain dominant, Integrated Full Electric Propulsion (IFEP) systems coupled with induction motors and Permanent Magnet Synchronous Motors (PMSMs) offer higher efficiency and lower emissions. Furthermore, wind-assisted technologies, such as Dynarigs, Flettner rotors, and towing kites, demonstrate great potential to reduce fuel consumption by up to 50% compared to conventional systems, while nuclear propulsion enables higher operational speeds with minimal fuel replenishment. However, key challenges remain, including high initial investment costs, control system complexity, and regulatory acceptance. In conclusion, the future of ship propulsion lies in hybrid configurations that optimize the combination of electric and wind power, supported by predictive computational models and fault-tolerant control to achieve cleaner, safer, and more sustainable maritime operations. Interdisciplinary collaboration is essential to accelerate this transition.